Komponen-Komponen Kurikulum Pendidikan Agama Kristen dalam Keluarga, Desain dan Pengembangannya, Rencana Pembelajaran, serta Implementasi Konkret (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to examine the components of the Christian Religious Education (CRE) curriculum in the family, its design and development, and its concrete implementation. The research employs a qualitative approach with a descriptive design through library research, using data sources such as books, academic journals, and relevant articles. The data were analyzed using descriptive qualitative techniques to produce a systematic and in-depth description. The findings show that the CRE curriculum in the family consists of interconnected components, namely objectives, content, strategies, methods, and evaluation, which must be implemented in an integrated manner. Faith education in the family is carried out through methods such as role modeling, habituation, teaching, discussion, mentoring, and practical application. Effective strategies include parental role modeling, dialogical communication, and love-based discipline. The implementation of the curriculum is realized through concrete activities such as family prayer, family worship, Bible reading, and the application of Christian values in daily life. In conclusion, the success of Christian Religious Education in the family largely depends on the active role and consistency of parents in implementing the curriculum in a holistic and continuous manner. With the right approach, the family can become an effective center of faith education in shaping children who are faithful, character-driven, and prepared to face life’s challenges.